Abiraterone-induced rhabdomyolysis resulting in acute kidney injury: A case report and review of the literature. (June 2018) - Dineen, Michael; Hansen, Elizabeth; Guancial, Elizabeth; Sievert, Lynn; Sahasrabudhe, Deepak
Abiraterone, a CYP17 inhibitor, blocks androgen biosynthesis in multiple tissue types. In combination with prednisone, it is approved as a first-line treatment for metastatic castration-resistant prostate cancer. We present a case of rhabdomyolysis associated with abiraterone therapy resulting in acute on chronic kidney injury in a patient with metastatic castration-resistant prostate cancer. Strict monitoring should be employed in patients started on abiraterone who have additional risk factors for developing rhabdomyolysis.